2010
DOI: 10.1007/s10597-010-9351-z
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Outcomes and Unmet Needs of a Cohort of Former Long-Stay Patients in Melbourne, Australia

Abstract: Former long-stay patients with psychotic disorders have significant unmet needs. This study assessed the long-term outcomes for the original cohort of 18 residents of the Footbridge Community Care Unit (CCU), a residential psychiatric rehabilitation unit at St Vincent's Mental Health Melbourne. A review of case records and interviews were conducted for each member of the cohort 8 years after admission to the CCU. Members of the cohort were living in a variety of settings after discharge from the CCU. Despite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…The period of community residence following discharge to the CCU was consistently reflected on favourably by members of the cohort, although for the majority of individuals this recovery was disrupted following discharge to alternative housing settings. In their more recent experience they identified a lack of somewhere stable to live and broader uncertainty about their future well-being [23]. These findings are mirrored by other studies that document the challenges faced by people without stable housing, in particular the challenge of recurrent dislocation from social supports and the risk of return to institutional care [40].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 56%
See 4 more Smart Citations
“…The period of community residence following discharge to the CCU was consistently reflected on favourably by members of the cohort, although for the majority of individuals this recovery was disrupted following discharge to alternative housing settings. In their more recent experience they identified a lack of somewhere stable to live and broader uncertainty about their future well-being [23]. These findings are mirrored by other studies that document the challenges faced by people without stable housing, in particular the challenge of recurrent dislocation from social supports and the risk of return to institutional care [40].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 56%
“…In-depth interviews with a cohort of former long-stay patients and CCU residents in Melbourne, Victoria, eight years after hospital discharge, confirmed that patients with persisting severe disabilities may face isolation and dislocation from community supports despite the experience of recovery in some aspects of their lives [23]. The 18 people studied were ageing former long-stay patients discharged from a CCU after several years -on average five years -of residential rehabilitation Members of the cohort reflected on the negative effects of prolonged institutional care, including loss of a social support network and lack of meaningful activities.…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 95%
See 3 more Smart Citations